Maternal and perinatal guideline development in hospitals in South East Asia: the experience of the SEA-ORCHID project - Short Jacki; Turner Tari J (BMC, 2009)
Abstract Background Clinical practice guidelines (CPGs) are commonly used to support practitioners to improve practice. However many studies have raised concerns about guideline quality. The reasons why guidelines are not developed following the established development methods are not clear. The SEA-ORCHID project aims to increase the generation and use of locally relevant research and improve clinical practice in maternal and perinatal care in four countries in South East Asia. Baseline data highlighted that development of evidence-based CPGs according to recommended processes was very rare in the SEA-ORCHID hospitals. The project investigators suggested that there were aspects of the recommended development process that made it very difficult in the participating hospitals. We therefore aimed to explore the experience of guideline development and particularly the enablers of and barriers to developing evidence-based guidelines in the nine hospitals in South East Asia participating in the SEA-ORCHID project, so as to better understand how evidence-based guideline development could be facilitated in these settings. Methods Semi-structured, face-to-face interviews were undertaken with senior and junior healthcare providers (nurses, midwives, doctors) from the maternal and neonatal services at each of the nine participating hospitals. Interviews were audio-recorded, transcribed and a thematic analysis undertaken. Results Seventy-five individual, 25 pair and eleven group interviews were conducted. Participants clearly valued evidence-based guidelines. However they also identified several major barriers to guideline development including time, lack of awareness of process, difficulties searching for evidence and arranging guideline development group meetings, issues with achieving multi-disciplinarity and consumer involvement. They also highlighted the central importance of keeping guidelines up-to-date. Conclusion Healthcare providers in the SEA-ORCHID hospitals face a series of barriers to developing evidence-based guidelines. At present, in many hospitals, several of these barriers are insurmountable, and as a result, rigorous, evidence-based guidelines are not being developed. Given the acknowledged benefits of evidence-based guidelines, perhaps a new approach to supporting their development in these contexts is needed.